Quo Vadis, Cohesion Policy? European Regional Development at a Crossroads - Thomas Schwab (Intereconomics, 2024)
European cohesion policy is undergoing a significant identity crisis, with debates intensifying over its fundamental goals and strategies for fostering regional development. Global challenges and shifting geopolitical dynamics further complicate the quest for successful regional development, introducing new trade-offs. This paper presents a comprehensive analysis of the core issues within this debate, explores their broader implications and proposes preliminary recommendations to address the emerging obstacles cohesion policy is facing.
Keywords: R11; O21; 330